Designing Stainless Steel Surfaces with Anti‐Pitting Properties Applying Laser Ablation and Organofluorine Coatings. Issue 6 (22nd January 2018) - Armelin, Elaine; Moradi, Sona; Hatzikiriakos, Savvas G.; Alemán, Carlos
Abstract : Long‐lasting and superhydrophobic stainless steel with anti‐pitting properties is achieved by modifying conventional AISI 304L through a two‐step strategy: 1) application of a femtosecond surface laser ablation treatment to generate micro‐nano structures on the surface; and 2) deposition of organofluorine nanometric coating. Samples with two different patterns, namely paraboloid‐ and cauliflower‐like, are approached and investigated by means of contact angle hysteresis, X‐ray photoelectron spectroscopy, and electrochemical techniques. Results indicate that the stainless steel surface acquires efficient anticorrosive properties due to the homogenization and refinement of the patterned microstructure into a magnetite rich phase, in combination with the formation of a carbonaceous and sol–gel layer. The adherent semiconducting oxide layer is stable over time in presence of an aggressive chloride environment. The prepared superhydrophobic surfaces prevent the steel substrates from getting wet with water, protecting them from the pitting corrosion caused by the electrolyte intrusion. The corrosion resistance is explained by a mechanism in which, in addition of the silane coating, the air trapped into the micro‐nano patterned surfaces plays an important role. Abstract : Long‐lasting and superhydrophobic stainless steel with anti‐pitting properties is achieved by modifying AISI 304L through a two‐step strategy:1) application of a femtosecond surface laser ablation; and 2) deposition of a nanometric coating. The prepared surfaces prevent the steel substrates from getting wet with water, protecting them from the pitting corrosion caused by the electrolyte intrusion.